A systematic review of rural-specific barriers to medication treatment for opioid use disorder in the United States. (3rd May 2020) - Lister, Jamey J.; Weaver, Addie; Ellis, Jennifer D.; Himle, Joseph A.; Ledgerwood, David M.
ABSTRACT: Background: Opioid-related deaths have risen dramatically in rural communities. Prior studies highlight few medication treatment providers for opioid use disorder in rural communities, though literature has yet to examine rural-specific treatment barriers. Objectives: We conducted a systematic review to highlight the state of knowledge around rural medication treatment for opioid use disorder, identify consumer- and provider-focused treatment barriers, and discuss rural-specific implications. Methods: We systematically reviewed the literature using PsycINFO, Web of Science, and PubMed databases (January 2018). Articles meeting inclusion criteria involved rural samples or urban/rural comparisons targeting outpatient medication treatment for opioid use disorder, and were conducted in the U.S. to minimize healthcare differences. Our analysis categorized consumer- and/or provider-focused barriers, and coded barriers as related to treatment availability, accessibility, and/or acceptability. Results: Eighteen articles met inclusion, 15 which addressed consumer-focused barriers, while seven articles reported provider-focused barriers. Availability barriers were most commonly reported across consumer (n = 10) and provider (n = 5) studies, and included the lack of clinics/providers, backup, and resources. Acceptability barriers, described in three consumer and five provider studies, identified negative provider attitudes about addiction treatment, and providers' perceptions of treatment as unsatisfactory for rural patients. Finally, accessibility barriers related to travel and cost were detailed in four consumer-focused studies whereas two provider-focused studies identified time constraints. Conclusions: Our findings consistently identified a lack of medication providers and rural-specific implementation challenges. This review highlights a lack of rural-focused studies involving consumer participants, treatment outcomes, or barriers impacting underserved populations. There is a need for innovative treatment delivery for opioid use disorder in rural communities and interventions targeting provider attitudes.